State-of-the-Art Room Temperature Operable Zero-Bias Schottky Diode-Based Terahertz Detector Up to 5.56 THz - Rahul Yadav; Florian Ludwig; Fahd Rushd Faridi; J. Michael Klopf; Hartmut G. Roskos; Sascha Preu; Andreas Penirschke (Sensors, 2023)
We present the characterization of a Zero-bias Schottky diode-based Terahertz (THz) detector up to 5.56 THz. The detector was operated with both a table-top system until 1.2 THz and at a Free-Electron Laser (FEL) facility at singular frequencies from 1.9 to 5.56 THz. We used two measurement techniques in order to discriminate the sub-ns-scale (via a 20 GHz oscilloscope) and the ms-scale (using the lock-in technique) responsivity. While the lock-in measurements basically contain all rectification effects, the sub-ns-scale detection with the oscilloscope is not sensitive to slow bolometric effects caused by changes of the IV characteristic due to temperature. The noise equivalent power (NEP) is 10 pW/<semantics><msqrt>Hz</msqrt></semantics> in the frequency range from 0.2 to 0.6 THz and 17 pW/<semantics><msqrt>Hz</msqrt></semantics> at 1.2 THz and increases to 0.9 <semantics>μ</semantics>W/<semantics><msqrt>Hz</msqrt></semantics> at 5.56 THz, which is at the state of the art for room temperature zero-bias Schottky diode-based THz detectors with non-resonant antennas. The voltage and current responsivity of ∼500 kV/W and ∼100 mA/W, respectively, is demonstrated over a frequency range of 0.2 to 1.2 THz with the table-top system.